Impact of a pediatric digital mental health intervention on caregiver sleep and stress: A retrospective exploration of moderators of improvement - Darian Lawrence-Sidebottom; Kelsey L McAlister; Donna McCutchen; Monika Roots; Jennifer Huberty (Digital Health)
Background Children's mental health (MH) places significant strain on their caregivers, who often experience disrupted sleep and heightened stress. Given the close relationship between caregiver and child MH symptoms, understanding how digital MH interventions (DMHIs) influence both child and caregiver symptoms is essential for optimizing family-centered treatment approaches. Objectives The purpose of this study was to (a) examine associations between child MH and caregiver sleep problems and stress before beginning MH treatment, (b) explore whether a child's engagement level with a DMHI moderates their rate of MH improvement, and (c) determine whether a child's rate of MH improvement is associated with their caregiver's rate of improvement in sleep problems and stress. Methods Child–caregiver pairs ( N  = 3104) completed assessments approximately monthly over at least three months of care to assess caregiver sleep problems and stress, and child MH outcomes. Associations between caregiver and child MH symptoms at baseline were tested. Linear mixed-effects models tested whether engagement was associated with child symptom improvements, and to test whether child outcomes were associated with monthly improvements in their caregiver. Results Caregiver sleep problems were associated with child internalizing symptoms (anxiety, depression, and sleep problems; P  < .001). Stress was associated with child externalizing symptoms (inattention, hyperactivity, and opposition; P < .001) and younger child age ( P < .001). Improvements in symptoms were marginally larger for children with more frequent coaching and therapy sessions ( P  = .066). Larger improvements in child symptoms were significantly associated with larger improvements in caregiver sleep problems and stress ( P s < .001). Conclusion Caregivers of children with more severe symptoms experienced higher stress and sleep disturbances. Greater session engagement was linked to greater child symptom improvement, and greater child symptom improvement was associated with greater reductions in caregiver sleep problems and stress. This highlights how a pediatric DMHI can drive meaningful improvements in MH that extend beyond the child, creating positive ripple effects for caregivers as well.